Unformatted text preview: = n +1 n − m ⎠
Now, the first three sums can be turned into a single sum if we pull out one of the redundant m=0 terms ( 1 ) from the first two sums and subtract off the m=n term n
( 21n ) that needs to be added write a single sum, k
k
1 ⎛1 1
1
1⎞
−
+∑
+∑
⎜ n 2n
⎟ . 2n ⎝
m = 1− n n + m
m = n +1 n − m ⎠
Now, replace m with j
n in the first sum, k
1 ⎛ 1 1 k+n 1
1⎞
S=
−
+∑ + ∑
⎜ n 2n
⎟ . 2n ⎝
j =1 j
m = n +1 n − m ⎠ S= Replace m with n+j in the last sum, 1 ⎛ 1 1 k+n 1 k−n...
View
Full
Document
This document was uploaded on 03/02/2014 for the course PHYS 435b at Western Nevada College.
 Spring '14
 D.Kagan

Click to edit the document details